2019
DOI: 10.1111/jfd.13086
|View full text |Cite
|
Sign up to set email alerts
|

Changes in physiology and virulence during the selection of resistant Yersinia ruckeri mutants under subinhibitory cefotaxime concentrations

Abstract: Bacterial antibiotic resistance is one of the main healthcare problems currently. Apart from reducing antibiotic efficacy, it has awakened the interest of scientists due to its association with bacterial fitness and virulence. Interestingly, antibiotic resistance can be a source of both increased fitness and decreased fitness, even though the molecular basis of these relationships remains unknown. The aim of this work is to define the effects of sub‐MIC concentrations of cefotaxime, an antibiotic extensively u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…The tissue organ distribution ( Figure 4 ) showed that, after treatment with 1/4MIC Amoxicillin and Tylosin, the amount of bacteria in the lung, liver, and spleen of the mice was significantly lower than that in the control group. We speculate that this may be caused by the down-regulation of virulence factors by sub-concentration antibiotics [ 35 ]. Furthermore, the results of tissue HE staining ( Figure 5 ) showed that, after treatment with 1/4MIC Amoxicillin and Tylosin, respectively, the damage degree of each tissue was significantly lower than that of the control group, which indicates that 1/4MIC Amoxicillin and Tylosin might be involved in the expression of multiple genes that regulate bacterial virulence [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…The tissue organ distribution ( Figure 4 ) showed that, after treatment with 1/4MIC Amoxicillin and Tylosin, the amount of bacteria in the lung, liver, and spleen of the mice was significantly lower than that in the control group. We speculate that this may be caused by the down-regulation of virulence factors by sub-concentration antibiotics [ 35 ]. Furthermore, the results of tissue HE staining ( Figure 5 ) showed that, after treatment with 1/4MIC Amoxicillin and Tylosin, respectively, the damage degree of each tissue was significantly lower than that of the control group, which indicates that 1/4MIC Amoxicillin and Tylosin might be involved in the expression of multiple genes that regulate bacterial virulence [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…In brief, the bacterium was cultivated in a nutrient broth, washed, and suspended in phosphate-buffered saline (PBS). The optical density of the bacterial suspension was adjusted to 0.5 at 600 nm ( 33 ). This suspension was serially diluted five times (1:10) by PBS.…”
Section: Methodsmentioning
confidence: 99%
“…There are several semisynthetic 3rd‐generation cephalosporins like cefotaxime, ceftriaxone, ceftazidime, cefixime and ceftiofur. These drugs have been examined for their antibacterial activity against bacterial fish pathogens (Blackburn et al., 2010; Chu et al., 2016; García‐Torrico et al., 2019; Kumar et al., 2015; Ottem et al., 2007; Rose et al., 2013), and some are possibly in use for some aquaculture purposes (Yanong, 2019).…”
Section: Introductionmentioning
confidence: 99%